Protective Effect of Alpha-Lipoic Acid on Cypermethrin-Induced Oxidative Stress in Wistar Rats. (October 2013) - Mignini, F.; Nasuti, C.; Fedeli, D.; Mattioli, L.; Cosenza, M.; Artico, M.; Gabbianelli, R.
Cypermethrin (CY), a class II pyrethroid pesticide, is globally used to control insects in the household and in agriculture. Despite beneficial roles, its uncontrolled and repetitive application leads to unintended effects in non-target organisms. In light of the relevant anti-oxidant properties of alpha-lipoic acid (ALA), in the work described herein we tested the effect of a commercially available ALA formulation on cypermethrin (CY)-induced oxidative stress in Wistar rats. The rats were orally administered with 53.14 mg/kg of ALA and 35.71 mg/kg of CY for 60 days. The treatment with CY did not induce changes in either locomotor activities or in body weight. Differences were observed on superoxide dismutase (SOD), catalase (CAT) and lipid peroxidation that were re-established by ALA treatment at similar levels of the placebo group. Furthermore, ALA formulation increased glutathione (GSH) level and glutathione peroxidase (GPx) activity. Because of the widespread use of CY, higher amounts of pesticide residues are present in food, and a diet supplementation with ALA could be an active free radical scavenger protecting against diseases associated with oxidative stress.